Analysis Of Inpatient Service Factors On Patient Satisfaction Level at Ngantang Community Health Center - Leo Abdul Azis; Heny Nurmayunita; Maulana Arif (Universitas Prima Indonesia, 2026)
The quality of healthcare services, particularly inpatient care at Community Health Centers (Puskesmas), is a key determinant of patient satisfaction. Although the Minimum Service Standards (SPM) target satisfaction above 95%, surveys in Indonesia show that satisfaction rates at Puskesmas remain in the range of 76–82%. This gap indicates the need for an in-depth evaluation of service factors.This study aims to analyze the relationship between five dimensions of service quality (Tangible, Assurance, Reability, Responsiveness, and Empathy) based on the SERVQUAL model with the level of satisfaction of inpatients at the Ngantang Community Health Center, Malang Regency. This study used a quantitative design with a correlation approach. The sample consisted of 39 inpatient respondents. Data analysis used univariate tests and Spearman's Rho correlation bivariate tests. The overall level of patient satisfaction was in the high category, where 90% (35 respondents) stated Satisfied. The results of the bivariate correlation test showed that only the Assurance variable had a statistically significant relationship with the level of patient satisfaction, with a p value of 0.032. Meanwhile, the dimensions of Tangible (p = 0.626), Reability (p = 0.843), Responsiveness (p = 0.301), and Empathy (p = 0.874) did not have a significant relationship with patient satisfaction (p > 0.05). There is a significant positive relationship between service assurance and inpatient satisfaction. This dimension, which encompasses the competence, friendliness, and credibility of staff, is a key factor that needs to be prioritized in efforts to improve service quality.